Study on The Analysis of Kemayoran Drainage Channel, Kemayoran Urban Village, Bangkalan Sub-District, Bangkalan Regency - Mohammad Eko Hadi Wibowo (NAROTAMA UNIVERSITY, Indonesia, 2022)
The success of development in Bangkalan regency is marked by the increase in housing and shops. The existence of changes in the spatial layout of Bangkalan city can increase surface runoff, causing roads and residential areas to experience puddles of water. The height of the flood inundation that occurs on average is at an elevation of 30 cm to 40 cm above the road surface. The Kemayoran drainage channel is an open channel, so the method used in this planning begins with a hydrological analysis which includes calculating the maximum daily rainfall at the study site for 10 years starting from 2011 to 2020, then calculating the design rainfall intensity using the Distribution method. Gumble, Normal Distribution, Log Normal Distribution, Log Pearson III Distribution, as well as a distribution match test was carried out to test whether the existing rainfall data matched the selected method. The suitability test used is the Chi-Square test and the Smirnov – Kolmogorov test. Next, an analysis of the planned flood discharge was carried out using the Rational method in which the calculation of the flow coefficient (C), the time of concentration (tc), and calculating the intensity of the rain was carried out. Furthermore, analysis of the discharge of the existing drain with the Manning formula is carried out to determine the maximum discharge capacity of the exhaust channel. From the calculation results, it is found that the planned discharge of the Kemayoran drainage channel for Q2 = 90,657 mm, Q5 = 116, 627 and Q10 = 133,627 mm, so that the results of these calculations indicate that the cross section of the xisting canal cannot accommodate the existing water The results obtained from the calculation show that, the existing channel cross section cannot accommodate the existing water discharge, so treatment is needed in the form of re-dimensioning the channel using a U-ditch with dimensions of 100,100,120.8 along 288 m, and using a trapezoidal stone pair with a channel width. 1.2 m and high 1.3 m long 872 m. In the short term, the handling of flooding and inundation that occurs in the Kemayoran drain can be done by normalizing the channel, so that the problem of flood inundation can be overcome for a return period of 2 years, 5 years, 10 years, 20 years and 50 years.